Optimal participation in decision-making in advanced chronic disease: perspectives of patients, relatives and physicians - Houska, Adam; Tučková, Anna; Vlčková, Karolína; Poláková, Kristýna; Loučka, Martin (Annals of palliative medicine, 2021)
BACKGROUND: Making decisions about health care issues in advanced illness is difficult and the participation of patients and relatives is essential. Most of the studies on shared decision-making focus on the interaction between patient and physician (dyadic interaction), while the role of relatives in triadic decision-making remains less explored. The aim of the study was to investigate the perceived importance of the role of the patient, the physician and the relative in the decision-making from their respective perspectives. METHODS: Patients (n=154) with advanced disease, their relatives (n=95) and physicians (n=108) were asked to rank the importance of their roles on the scale from 0 to 10. Differences between respondent groups were examined by ANOVA. A typology of answers was constructed for dyadic and triadic relations and analyzed by descriptive statistics and the chi-square test. RESULTS: Physicians rated the importance of patients' role in decision-making significantly higher [mean 9.31; 95% confidence interval (CI): 9.07-9.55] than did patients themselves (mean 7.85; 95% CI: 7.37-8.32), while patients and relatives rated higher the importance of the physicians' role (mean 9.29; 95% CI: 8.98-9.59 and mean 9.20; 95% CI: 8.96-9.45, respectively) than did physicians themselves (mean 8.35; 95% CI: 0.06-8.65). In the analysis of the patient-physician dyadic interaction, patients ranked their role as equally important (44.1%) or more important (11.2%) than the role of physicians. Physicians (56.5%) thought patients should play a more important role. When relatives were included in the analysis, patients either preferred equal role of the three actors (30.2%) or prioritized the role of the physician and the relatives (16.8%), while physicians and relatives prioritized the role of the patient (54.6% and 29.0%, respectively). All results were statistically significant (P<0.05). CONCLUSIONS: Physicians and relatives tend to accentuate the active role of patients, while patients mostly prefer shared decision-making. Physicians seem to underestimate the importance of the role of relatives, compared to patients and relatives for whom the participation of relatives in the decision-making is of greater importance. A triadic decision-making model that acknowledges the importance of all three actors should be implemented in decision-making process in advanced illness.
Keywords: Decision Making; autonomy; Chronic Disease; palliative care; zapojení pacienta; Decision making; rozhodování; Humans; Patient Participation; Physicians; lidé; Physician-Patient Relations; vztahy mezi lékařem a pacientem; chronická nemoc; lékaři; advanced disease; participation; end of life